Rhabdias filicaudalis n. sp. (Nematoda: Rhabdiasidae) from the snake Spilotes pullatus (Serpentes: Colubridae) in Brazil - Barrella, T. H. [UNESP]; dos Santos, K. R.; da Silva, R. J. [UNESP] (Cambridge University Press, 2010)
Rhabdias filicaudalis n. sp. (Nematoda: Rhabdiasidae) from the lung of Spilotes pullatus (Serpentes: Colubridae) is described. The host snake was captured in the municipality of Avare, São Paulo State, Brazil. Rhabdias filicaudalis n. sp. differs from all other species by the combination of the following characters: straight body, truncated anterior end, six weakly developed lips arranged in two opposite groups of three, pre-equatorial vulva, oesophagus length/body length ratio (%) 4.9-7.5 (5.8 +/- 0.6), nerve ring distance from anterior end/oesophagus length ratio (%) 36.9-61.1 (49.8 +/- 6.4), tail length/body length ratio (%) 3.0-5.5 (4.0 +/- 0.5), vulva distance from anterior end/body length ratio (%) 39.9-51.7 (45.9 +/- 3.5), and a cuticular filiform tail tip.